Qualidade dos registros de enfermagem em prontuários após ação educativa em uma instituição pública de saúde - Silva, Ludimila Cristina Souza (2017)
Records in hospitalized patients' records are important for the communication of health professionals for continuity of care, cost measurement, quality assessment, as well as providing legal actions for teaching and research. Objective: To evaluate the quality of nursing records in patient records after an educational action. Methodology: An analytical descriptive study performed in Neonatal, Maternal and Child Intensive Care Units, with analysis of 45 charts, before and after an educational intervention, which lasted eight hours. To evaluate the quality, the Nursing Annotations Audit Form (HADDAD, 2004) was used. After the data collection, the data were analyzed using the STATA software. Results: The main nonconformities found in the records were: incorrect or incomplete records, illegible letters or erasures and absence of records. Among the nonconformities was the inadequate completion of the cases evaluated before and after the educational intervention. However, the means inherent to complete, incomplete and unfilled information were significantly better after the educational intervention (p> 0.05). The categories, identification data (PP = 81.16%) and execution of medical orders (PP = 89.13%), presented higher adequacy indexes with respect to the complete records. However, the nursing prescription (PP = 6.76%) overcame the nonconformities in the question of incorrect filling of records in patients' records. Conclusion: The educational action signaled positive results regarding the effectiveness of records in medical records, evidencing the importance of qualification of health professionals. Based on these evidences, a permanent education program is recommended, with the objective of qualifying professionals regarding the requirements of the work process, such as the elaboration of standardized protocols, the habit of recording the actions in a complete and objective manner, printed, among other aspects. Intervention actions can raise awareness among professionals about competence, commitment to safety and continuous improvement of the quality of care provided to the patient.